2002
DOI: 10.1126/science.1073263
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Regulation of Retinal and Pituitary Precursor Cell Proliferation

Abstract: Mammalian organogenesis requires the expansion of pluripotent precursor cells before the subsequent determination of specific cell types, but the tissue-specific molecular mechanisms that regulate the initial expansion of primordial cells remain poorly defined. We have genetically established that Six6 homeodomain factor, acting as a strong tissue-specific repressor, regulates early progenitor cell proliferation during mammalian retinogenesis and pituitary development. Six6, in association with Dach corepresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
242
0
3

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(263 citation statements)
references
References 24 publications
18
242
0
3
Order By: Relevance
“…Six gene products are characterized by the Six domain and Six-type homeodomain, which are required for specific DNA binding activity and function as transcription factors (Kawakami et al, 1996;Spitz et al, 1998;Ohto et al, 1999;Li et al, 2002;Lagutin et al, 2003). At present, six members of the family have been identified in mammals, and all members show a spatiotemporally regulated pattern of expression during embryogenesis, suggesting their involvement in embryonic development (Seo et al, 1999;Kawakami et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Six gene products are characterized by the Six domain and Six-type homeodomain, which are required for specific DNA binding activity and function as transcription factors (Kawakami et al, 1996;Spitz et al, 1998;Ohto et al, 1999;Li et al, 2002;Lagutin et al, 2003). At present, six members of the family have been identified in mammals, and all members show a spatiotemporally regulated pattern of expression during embryogenesis, suggesting their involvement in embryonic development (Seo et al, 1999;Kawakami et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Plus particulièrement, la protéine Six3 contrôlerait négative-ment l'expression de Wnt1 en se liant directement au niveau des séquences régulatrices de ce gène [15]. L'invalidation fonctionnelle de Six6 chez la souris n'est pas létale comme celle de Six3, mais conduit néanmoins à une hypoplasie hypophysaire et à une hypoplasie rétinienne (due à l'absence de nerf et de chiasma optique) [16]. transitoire.…”
Section: Six3/six6unclassified
“…De plus, le complexe Six6/Dach1 contrôlerait directement l'expression du gène p27 Kip1 (codant pour un inhibiteur des kinases dépendantes des cyclines). Les hypoplasies observées apparaissent ici corrélées à un défaut de prolifération des cellules précurseurs [16]. Il est à noter cependant que l'invalidation fonctionnelle de Dach1 n'entraîne pas de défauts de prolifération, ni d'hypoplasie hypophysaire chez la souris [17], bien que les nouveau-nés meurent à la naissance pour une raison encore indéterminée [18].…”
Section: Six3/six6unclassified
“…Moreover, Six3 was determined to be a direct negative regulator of Wnt1 expression in chick and fish embryos (Lagutin et al, 2003). In contrast, inactivation of Six3 function resulted in the lack of forebrain and eyes in O. latipes (Carl et al, 2002), and the targeted disruption of mouse Six3 and Six6 caused anterior truncation of forebrain and retinal hypoplasia, respectively (Li et al, 2002;Liu et al, 2006). Additionally, as a transcriptional repressor (Kobayashi et al, 2001), Six3 was shown to play a very crucial role in stimulating cell proliferation of D. rerio and X. leavis eye development (Tessmar et al, 2002).…”
Section: Introductionmentioning
confidence: 99%